2006
DOI: 10.1002/eji.200636138
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ICOS/B7RP‐1 T cell costimulatory pathway in murine experimental autoimmune uveoretinitis

Abstract: ICOS/B7RP-1 is a new member of the CD28/B7 family of costimulatory molecules and plays differential roles in autoimmune diseases. In this study, we examined the role of ICOS/B7RP-1 pathway in the pathogenesis of mouse experimental autoimmune uveoretinitis (EAU), an animal model of human autoimmune uveitis. ICOS expression was found on infiltrating CD4 + T cells in the region of the retina in EAU-induced mice. The anti-B7RP-1 monoclonal antibody (mAb)-treated or ICOS-deficient mice showed a substantial reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…These results strongly suggested that the ICOS/B7RP-1 co-stimulatory pathway plays a critical role in EAU. Notably, our observations differ somewhat from Yoshihiko Usui's report that blockade of ICOS/B7RP-1 by anti-B7RP-1 mAb during the induction phase of EAU in mice exhibited no effect, and that the disease was reduced by blocking the ICOS/B7RP-1 interaction during the effector phase [29]. Such differences may result from alternate negative regulation of the ICOS/B7RP-1 pathways and species-specific differences.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…These results strongly suggested that the ICOS/B7RP-1 co-stimulatory pathway plays a critical role in EAU. Notably, our observations differ somewhat from Yoshihiko Usui's report that blockade of ICOS/B7RP-1 by anti-B7RP-1 mAb during the induction phase of EAU in mice exhibited no effect, and that the disease was reduced by blocking the ICOS/B7RP-1 interaction during the effector phase [29]. Such differences may result from alternate negative regulation of the ICOS/B7RP-1 pathways and species-specific differences.…”
Section: Discussioncontrasting
confidence: 80%
“…Prior research on the ICOS pathway was performed via gene knockout and systematic antibody blockage [24,29]. However, all the treatments of systemic administration have the mutual disadvantage of hypoimmunity that may limit clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ICOS signaling is also implicated in autoimmune disorders and graft versus host disease. For instance, ICOS blockade by treatment with anti-B7RP-1 monoclonal Ab or genetic inactivation substantially reduced clinical progression of murine experimental autoimmune uveoretinitis (45), whereas targeting of ICOS expressed on alloreactive donor T cells inhibited graft versus host disease and promoted bone marrow engraftment in recipient mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have however shown the reverse: in mice given sheep anti-glomerular basement membrane antibodies, the resultant nephritis is exacerbated by blocking OX40L antibody with increased IFNγ+T cell infiltration [129]. A second study reported in abstract form only reports exacerbation of EAU with OX40L blockade, although this is in contrast to other EAU and EAE studies [130][131][132][133].…”
Section: Ox40 and Ox40l Ameliorate Autoimmunity In Vivomentioning
confidence: 91%